Research and writing in international relations - Roselle, Laura; Shelton, Joel T. (Routledge, 2020)
"Research and Writing in International Relations, Third Edition, offers the step-by-step guidance and the essential resources needed to compose political science papers that go beyond description and into systematic and sophisticated inquiry. This book provides concise, easy-to-use advice to help students develop more advanced papers through step-by-step descriptions, examples, and resources for every stage of the paper writing process. The book focuses on areas where students often need guidance: understanding how international relations theory fits into research, finding a topic, developing a question, reviewing the literature, designing research, and last, writing the paper. Including current and detailed coverage on how to start research in the discipline's major subfields, Research and Writing in International Relations gives students a classroom-tested approach that leads to better research and writing in introductory and advanced classes."-- Provided by publisher.